The path to poverty reduction: How do economic growth and fiscal policy influence poverty through inequality in Indonesia? - Agussalim Agussalim; Nursini Nursini; Sultan Suhab; Randi Kurniawan; Salman Samir; Tawakkal Tawakkal (Economies, 2024)
One of the factors impeding the decline in poverty in Indonesia is the government's lack of attention to the need to reduce income inequality. Fiscal policy and economic growth can effectively reduce poverty by lowering income inequality, so the inequality channel must be considered. Socioeconomic and infrastructure differences between provinces can influence the effectiveness of economic growth and fiscal policy in reducing poverty. This study aimed to assess the effects of economic growth and fiscal policy regarding spending and taxes on direct and indirect poverty reduction through lowering income inequality, as well as considering how these variables influence poverty by province. This study employed secondary data, including panel data for 2010-2023 from 34 provinces in Indonesia, which were analyzed using autoregressive cross-lagged SEM. This study found that economic growth and fiscal policy regarding spending on education and health are statistically significant in directly reducing poverty in regions outside Java but do not affect it through income inequality. Taxes increase income inequality, and the social safety net does not reduce poverty outside Java. The increased spending on education and health should continue, but improvements are needed in terms of targeting social safety nets and tax reforms to strengthen the system and reduce inequality.
Keywords: 330; poverty; income inequality; economic growth; fiscal policy; panel data